ANALISIS PENGARUH DESIGN AESTHETIC USER INTERFACE IOS TERHADAP BEHAVIOR PENGGUNA DI SURABAYA MELALUI INTENTION TO USE - Cahyono, Sugiharto Adhi; Fianto, Achmad Yanu Alif; Bahruddin, Muh (Jurnal Art Nouveau, 2015)
Abstract: This study aimed to analyze the influence of aesthetic design of the user interface of iOS user behavior in Surabaya through intention to use. Research using quantitative research methods manifold verification. The approach used is the approach of causality (causality research) with explanatory survey research model (explanatory survey). Models were selected because researchers investigating possible causal relationship of an phenomenon. The samples used in this research were 105 respondents. The research instrument used in the form of a structured questionnaire distributed by accidental sampling method. The data obtained were processed by the method of analysis GeSCA. Results of this research confirms, that the design aesthetic and intention to use is a determinant of usage behavior, because the design aesthetic and intention to use can encourage of usage behavior on iOS devices. Design aesthetic and intention to use jointly affect usage behavior. Theoretically, the model found in this study also explains the role of intention to use as a mediating variable between the design aesthetic of the iOS device and user behavior.Â Keywords : design aesthetic, user interface, behavior, intention, iOS